Challenges Related to Children Faced by Kindergarten Teachers of Children with Autism Spectrum Disorder in Improving Their Quality of Life - Nassar, Rajaa Ebrahim (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the challenges related to the child, the educational environment, and the teacher that affected the quality of life among kindergarten teachers of children with autism spectrum disorder in Araba Batouf city. A qualitative descriptive approach was adopted, and a purposive sample of 10 kindergarten teachers in Araba Batouf was selected. Semi-structured interviews were used as the primary data collection tool after they were developed based on the latest literature (2020–2025), validated by experts in education, psychology, and special education, and pre-tested for clarity and reliability. The findings revealed significant difficulties in communicating with the children, diverse individual needs, a lack of specialized educational resources, and the negative impact of work-related stress on the teachers’ psychological and emotional well-being. The study underscored the importance of providing a stimulating educational environment and implementing training programs to enhance teachers’ skills in addressing these challenges while achieving a work–life balance. It recommended the development of specific quality standards for kindergartens and the establishment of sustainable support mechanisms adapted to the local context of Araba Batouf.